Simultaneous automatic electrochemical detection of zinc, cadmium, copper and lead ions in environmental samples using a thin-film mercury electrode and an artificial neural network - Kudr, Jiri; Nguyen, Hoai Viet; Gumulec, Jaromir; Nejdl, Lukas; Blazkova, Iva; Ruttkay-Nedecky, Branislav; Hynek, David; Kynicky, Jindrich; Adam, Vojtech; Kizek, Rene (Sensors (Basel, Switzerland), 2014)
In this study a device for automatic electrochemical analysis was designed. A three electrodes detection system was attached to a positioning device, which enabled us to move the electrode system from one well to another of a microtitre plate. Disposable carbon tip electrodes were used for Cd(II), Cu(II) and Pb(II) ion quantification, while Zn(II) did not give signal in this electrode configuration. In order to detect all mentioned heavy metals simultaneously, thin-film mercury electrodes (TFME) were fabricated by electrodeposition of mercury on the surface of carbon tips. In comparison with bare electrodes the TMFEs had lower detection limits and better sensitivity. In addition to pure aqueous heavy metal solutions, the assay was also performed on mineralized rock samples, artificial blood plasma samples and samples of chicken embryo organs treated with cadmium. An artificial neural network was created to evaluate the concentrations of the mentioned heavy metals correctly in mixture samples and an excellent fit was observed (R2 = 0.9933).
Keywords: kur domácí; automatizace; olovo; Lead; Copper; životní prostředí; Electrodes; geologické sedimenty; regresní analýza; Chickens; neuronové sítě; těžké kovy; Environment; rtuť; Mercury; Neural Networks, Computer; Electrochemistry; kalibrace; Robotics; elektrody; Geologic Sediments; Automation; Animals; lidé; elektrochemie; robotika; Humans; zvířata; zinek; Regression Analysis; měď; ionty; kadmium; Metals, Heavy; Ions; Calibration; Zinc; Cadmium